Silicon nanoparticles synthesized using a microwave method and used as a label‐free fluorescent probe for detection of VB12. (22nd May 2019) - Long, Yao; Zhang, Li; Yu, Ying; Lin, Bixia; Cao, Yujuan; Guo, Manli
Abstract: A simple and rapid detection strategy for vitamin B12 (VB12 ) was established based on label‐free silicon quantum dots (SiQDs); the detection mechanism was additionally investigated. SiQDs were synthesized using a one‐step microwave method, and their fluorescence was stronger than that synthesized using the hydrothermal method. SiQDs fluorescence was quenched using VB12 due to the inner filter effect (IFE), which was demonstrated using ultraviolet (UV) absorption spectra, fluorescence lifetime, transmission electron microscopy and zeta potential analysis. Subsequently, quercetin (Que) and doxorubicin (Dox) with absorption peaks that overlapped the excitation or emission peaks of SiQDs respectively were used as control groups to investigate the quenching mechanism. Results showed that quenching efficiency was related to the level of overlap between the adsorption peak of the quencher and the excitation or emission peaks of SiQDs. A greater level of overlap caused a higher quenching efficiency. Therefore, the sensitive quenching of VB12 for SiQDs was due to the synergistic effect of the synchronous overlap between the absorption peak of VB12 with the excitation and emission peaks of SiQDs. Fluorescence quenching efficiency increased linearly in the 0.5 to 16.0 μmol·L −1 VB12 concentration range, and the detection limit was 158 nmol·L −1 . In addition, SiQDs were applied to determine VB12 in tablets and human urine samples with satisfactory recoveries ranging from 97.7 to 101.1%.